Corporate labor welfare and professional development: the case of an Ecuadorian banana company - Sánchez Zambrano, Serela F. (2024)
The importance of workplace well-being lies in improving the quality of life of workers, which results in work performance and therefore in the productivity and significance of the company. To this end, more and more measures are being adopted that address these issues, one of which is dual vocational training. The purpose of this study was to analyze professional development through a dual professional training process carried out in a banana company in Ecuador. A mixed methodology was applied where the quantitative analysis technique was incorporated to complement the qualitative results. It took as reference the items proposed for work well-being and the direct observation carried out by the Social Worker. The sampling was intentional, selecting 7 workers from different departments who participated in training programs. Discourse analysis was applied. The results revealed that the workers participated in the training to improve and update their knowledge for their area of ​​work, that they felt recognized by both their bosses and their coworkers, and that their work was attractive. All of them had salary increases after completing the training. It is concluded that the training programs developed in companies contribute to improving the quality of life, performance and productivity; and that Social Work can contribute significantly to its implementation.